Comparing KAP regarding Halal pharmaceuticals among general practitioners and hospital doctors - Saleha Sadeeqa, Azmi Sarriff (Journal of Applied Pharmaceutical Science, 2014)
There is an increasing awareness amongst Muslim consumers to avoid all items containing non-Halal ingredients including medications. General practitioners and hospital doctors, in their practice encounter with the patients of different severity of illness, and accordingly their exposure to different categories of medicines will also be different. It therefore, needed for a study to compare knowledge, attitude and perception (KAP) of general practitioners and hospital doctors regarding Halal pharmaceuticals. This was a cross-sectional study using a structured, self-administered questionnaire to compare the knowledge, attitude and perception regarding Halal pharmaceuticals, among general practitioners and doctors working in various government hospitals in Malaysia. Results revealed that significant difference in the perception of general practitioners and hospital doctors was found. Significant difference was also found in some of statements of knowledge and attitude. This is concluded that general practitioners and hospital doctors differ in knowledge, attitude and perception regarding Halal pharmaceuticals. P≥ 0.05 was taken as statistically significant.
Keywords: Knowledge, Attitude, Perception, KAP, Halal, pharmaceuticals